The Relationship of Students’ Conceptual Mastery and Problem Solving on Rigid Body - Firmanilah Kamil; Parno Parno; Arif Hidayat (Pascasarjana Universitas Negeri Malang (UM), 2019)
Abstract: This study aims to determine the relationship between students mastery of concepts and problem solving on the rigid body lesson. This research was a correlational study. The research sample consisted of 64 students of 12th class of the state senior high schools were selected using purposive random sampling. The research instrument consisted of multiple choice questions to measure students ‘mastery of concepts and problem descriptions to measure students’ problem-solving. The average value of students’ mastery of concepts and problem solving students respectively were 52.81 (11.98) and 31.95 (10.06). Data results of both tests were analyzed with Pearson product moment correlation. The results showed a positive correlation between mastery of concepts to problem-solving student.Key Words: mastery of concepts, problem solving, rigid bodyAbstrak: Penelitian bertujuan untuk mengetahui hubungan antara penguasaan konsep dan pemecahan masalah siswa pada materi benda tegar. Jenis penelitian adalah penelitian korelasional. Sampel penelitian terdiri dari 64 siswa kelas XII dari dua sekolah SMA Negeri yang dipilih menggunakan purposive random sampling. Instrument terdiri dari soal pilihan ganda untuk mengukur penguasaan konsep dan uraian untuk mengukur pemecahan masalah. Rata-rata nilai penguasaan konsep dan pemecahan masalah berturut-turut adalah 52,81(11,98) dan 31,95(10,06). Data hasil kedua tes dianalisis dengan korelasi pearson product moment. Hasil penelitian menunjukkan adanya korelasi positif antara penguasaan konsep dengan pemecahan masalah siswa.Kata kunci: penguasaan konsep, pemecahan masalah, benda tegar